Geomorphological Cartography in Very High-Resolution Images: A proposal for linear erosion systems - Lupinacci, Cenira Maria [UNESP]; Stefanuto, Estêvão Botura; de Magalhães, Danilo Marques [UNESP] (Revista Brasileira de Geografia Fisica, 2025)
Accelerated linear erosion is a phenomenon frequently identified and studied in national and international literature. The aim of this paper is to discuss the possibilities of creating geomorphological mappings that enable the monitoring and support the management of linear erosion systems, based on the use of very high-resolution images, obtained with the use of unmanned aerial vehicles (UAVs). The working hypothesis is that geomorphological mapping, by spatializing the various linear erosive features, can collaborate with the identification of the most active sectors and assist in the management and containment of linear erosive features. The mapping made it possible to identify detailed features of the erosion system, allowing its dynamics to be evaluated and to identify more active sectors. Procedures and symbols are presented that can be replicated for geomorphological mapping using very high-resolution images.
Cartografia Geomorfológica em Imagens de Altíssima Resolução: Uma proposta para sistemas erosivos lineares
Keywords: Gully; Ravines; Symbology